Use of Thrombopoietin Receptor Agonists in Childhood Immune Thrombocytopenia - Garzon, Angelica Maria; Mitchell, William Beau (Frontiers in Pediatrics, 2015)
Most children with immune thrombocytopenia (ITP) will have spontaneous remission regardless of therapy, while about 20% will go on to have chronic ITP. In those children with chronic ITP who need treatment, standard therapies for acute ITP may have adverse effects that complicate their long term use. Thus, alternative treatment options are needed for children with chronic ITP. Thrombopoietin receptor agonists (TPO-RA) have been shown to be safe and efficacious in adults with ITP, and represent a new treatment option for children with chronic ITP. One TPO-RA, eltrombopag, is now approved for children. Clinical trials in children are ongoing and data is emerging on safety and efficacy. This review will focus on the physiology of TPO-RA, their clinical use in children, as well as the long term safety issues that need to be considered when using these agents